Role of emotional creativity and achievement motivation on trauma symptoms among university students - Bulathwatta, Asanka; Lakshika, Rekhani (Frontiers in Psychology, 2023)
The aim of this study was to understand the levels of trauma symptoms and the mediating role of achievement motivation, along with emotional creativity, among university students. Many students from various faculties exhibit diverse levels of academic motivation due to their program structures. However, the traumatic experiences faced by students and the subsequent post-traumatic symptoms can lead to various psychosocial and emotional consequences among university students, potentially impacting their emotional creativity and achievement motivation. The present study employed a quantitative approach, utilizing measures to assess emotional creativity, achievement motivation, and trauma symptoms within the sample. The sample under investigation comprised 337 undergraduates from nine different faculties at the University of Peradeniya, Sri Lanka. The study's results indicate a significant correlation between emotional creativity and achievement motivation. While emotional novelty did not display a significant correlation with achievement motivation, emotional effectiveness and authenticity did show such a correlation. Notably, hyperarousal, as a trauma symptom, exhibited a negative correlation with achievement motivation. The study identified both direct and indirect impacts of emotional creativity on achievement motivation. The findings from regression analysis suggested that the impact of emotional creativity on achievement motivation falls between higher and lower levels. Furthermore, the study concluded that trauma symptoms mediate the relationship between emotional creativity and achievement motivation among undergraduates.